Multicomponent iterative methods solving stationary problems of mathematical physics - Abrashina-Zhadaeva, Natali G.; Egorov, Alexey A. (Mathematical Modelling and Analysis, 2008)
Additive iterative methods of complete approximation for stationary problems of mathematical physics are proposed. The convergence rate in the case of an arbitrary number of commutative and noncommutative partition operators is analysed. The optimal values of the iterative parameter are found and related estimates for the number of iterations are derived. Some applications of suggested iterative methods are discussed. First Published Online: 14 Oct 2010